An explanatory study on the recruitment and selection process of the sales officers of Square Toiletries Limited - Mohin, Rafiqul Ahsan (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.